Potensi Curcumin sebagai Modalitas Terapi Suportif Pada Pasien Kanker Payudara - Amira Puri Zahra; Ahmad Farishal; Bintang Abadi Siregar (Majority, 2020)
Breast cancer is a malignancy in breast cells in the ducts or lobes due to mutations in gene level. Gene mutations, especially BRCA1 and BRCA2, are the dominant genes in breast cancer that activate carcinogenesis that causes immune defects. Decreased immunity must be improved and supported one of them using special nutrition improvements that have supportive therapy in breast cancer. Curcumin has potential as a nutrient that increases immunity and has an apotosis effect, suppresses metastases, regulates microRNA and stops the angiogenesis process promoted by VEGF in cancer cells. Curcumin is a natural ingredient obtained from Curcuma longa alias turmeric which has been used widely as a spice in the Asian region. The potential anticancer and antioxidant available in curcumin should be given at a minimum dose of 3.6gram and absorbed by the intestine only 1% but it is easily deposited in the brain, liver and lungs. The use of nano and injection routes are expected to increase the bioavability of curcumin.